STRATEGI MARKETING INDUSTRI MUSIK PADA ERA DIGITAL DI Indonesia - RR Ella Evrita H, S. E, M.M, RR Ella Evrita H, S. E, M.M; Ahmad Budi Sulistioyuwono, S. E, M.M,, Ahmad Budi Sulistioyuwono, S. E, M.M,; Fransiskus Rendy, B. Com, M.A.B, Fransiskus Rendy, B. Com, M.A.B (Akademi Komunikasi SAE Indonesia, 2022)
This concentrate on we will examine what digitalization in the music business means for music advertising This has a major effect based on music industry in conditions of music promoting and for purchasers as far as getting a charge out of music. Real time features have become something extremely powerful in the advanced period that we know as industry 4.0. The music business can no longer depend on actual items and buyers are currently more particular in getting a charge out of music. The strategy utilized in this study is a subjective technique with a phenomenological research methodology concerning what is capable by research subjects, for example, practices, insights, inspirations, activities, and so on comprehensively and through portrayals in the type of words and dialects. The consequences of this study are thatfor purchasers it is simpler to track down music and industry players are extremely strong of digitalization in the music business since it makes it simpler to advertise their music and assist with safeguarding their scholarly propertybecause it diminishes theft